The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.5021/ad.2014.26.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Association ofCYP2C9Genetic Variants with Vitiligo

Abstract: BackgroundVitiligo is a depigmenting skin disorder in which genetic factors play an important role.ObjectiveTo examine the association of CYP2C9 *1/*2/*3 gene polymorphism with vitiligo.MethodsIn this case controlled study, 95 Saudi patients with vitiligo (50 men and 45 women), with a mean age of 27.3 years, were analyzed. Patients were compared to 86 healthy controls from the same locality (76 men and 10 women), with a mean age of 20.1 years. In all participants, DNA was extracted and processed for characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
2
1
Order By: Relevance
“…The increase in the frequency of isolates of S. aureus resistant to β-lactam antibiotics has been reported in the literature since the beginning of its clinical use in 1940 (Livermore, 2000). Alzolibani et al (2012) found 96.7% ampicillin resistance in clinical isolates of S. aureus, which agrees with the data obtained in our study.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The increase in the frequency of isolates of S. aureus resistant to β-lactam antibiotics has been reported in the literature since the beginning of its clinical use in 1940 (Livermore, 2000). Alzolibani et al (2012) found 96.7% ampicillin resistance in clinical isolates of S. aureus, which agrees with the data obtained in our study.…”
Section: Resultssupporting
confidence: 83%
“…Similarly, Kowalski et al (2003) suggest that S. aureus had increased susceptibility to fourth generation fluoroquinolones. In contrast, other studies revealed high frequency of resistance to ciprofloxacin (Alzolibani et al, 2012;Flamm et al, 2012;Kwak et al, 2013). A possible explanation for this discrepancy could be that the isolates tested in this study were collected in the late 70s and early 80s prior to the introduction of fluoroquinolones to clinical use.…”
Section: Resultscontrasting
confidence: 45%
“…Third, the results of the Egger tests revealed the possibility of a significant publication bias in this meta-analysis. Moreover, vitiligo may also be modulated by several other genetic markers other than TNF-α, such as CYP2C9 (Alzolibani et al, 2014), PTPN22 (Garcia-Melendez et al, 2014), and ACE (Badran et al, 2015). Therefore, the results of our metaanalysis emphasize the need for further evaluation of the potential gene-gene interactions in vitiligo, in order to elucidate the pathogenesis of vitiligo.…”
Section: Discussionmentioning
confidence: 89%
“…Female predominance is seen in the present study (62% vs. 38%), similar to the results in studies done by Jaisankar et al and Al-Jabari et al 1,2 Studies with male predominance were not found among children in contrast to that among adults (Shankar et Kar [51.6%]). [3][4][5][6] So, there is more concern amongst parents in India when a girl is developing depigmented lesion than a boy as cosmetic appearance and related social and marital problems are more among girls in Indian structure.…”
Section: Discussionmentioning
confidence: 99%